Beyond Individual Resilience: Communal Ecology, Social Capital, and Systemic Barriers among Yogyakarta Tour Guides - Caecilia Dian Eka Piemiastuti; FX. Wahyu Widiantoro (Sean Institute, 2026)
This study reconceptualizes resilience from an individual-focused concept to a collective framework called “communal ecology,” in order to better understand how tour guides in the tourism industry cope with systemic barriers and uncertainty. Using a qualitative approach, the study conducted in-depth interviews with 10 professional tour guides in Yogyakarta, Indonesia, and analyzed the data thematically. The findings show that communal resilience is shaped by three key pillars: social capital (bonding and bridging) reflected in peer support and faith-based coping strategies, adaptive learning systems through professional associations that enhance knowledge sharing and collective self-efficacy, and the collective negotiation of systemic constraints such as regulatory pressures and market instability. These results extend the Transactional Stress Model by identifying communal social capital as a key resource and enrich the Challenge Metamorphosis Model by introducing the concept of communal ecology. Overall, the study concludes that resilience among tour guides is not merely an individual trait but a socially embedded and collective process driven by communal networks and adaptive collaboration, although its findings are limited by a small sample size and a single geographic context.